Nostalgia of Thaipusam celebration during the Covid-19 pandemic - Premalatha Karupiah, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Nostalgia is an emotion that has meaning associated to a group or community of people. Similar to other type of emotions, nostalgia is learnt and interpreted through social relationships. Nostalgia is associated with the recollection of the past; often something with special meaning to a person or a group of people. Nostalgia is often associated with past positive experiences that brought joy, pleasure, or happiness. It may bring happiness or sadness, but studies have shown that it brings more positive emotions compared to negative emotions. This article focuses on the nostalgia of participating in Thaipusam prior to the pandemic. Thaipusam is a Hindu festival celebrated mostly in places where there is a large group of Tamil Hindus. In Malaysia, Thaipusam is not merely a Hindu festival, it is attended by people of various religious background and culture. This is a qualitative study with data collected by interviewing five women living in Kedah who have attended Thaipusam in Penang for more than four decades. There was no celebration of Thaipusam in 2021 due to the pandemic. For the first time in their lives they were not part of this important festival. Their experiences shows both collective and individual nostalgia. Sharing nostalgia is seen as a way of going through a lonely period in their lives. They also shared how they used online darshan to go through this difficult period. Their experiences may be expressed as personal, but it is often related to their collective identity as a Malaysian Indian and as a member of a minority community.